Evaluation of the match between anthropometric measures and school furniture dimensions in Chile - Castellucci, H. I. (2016)
BACKGROUND:Students are exposed to the first systematic tasks or activities that a human being carries out in his/her life while at school. In this workplace situation, school furniture is a key factor for the adoption of proper body posture. OBJECTIVE:The aim of this paper was to observe and determine the potential mismatch between school furniture dimensions and anthropometric characteristics of the students from the Valparaíso region of Chile. METHODS:The sample consisted of 3,078 volunteer participants from 18 schools (public, semi-public, private). Eight anthropometric measures were gathered, together with six furniture dimensions. Mismatch analyses were carried out by using pre-defined mismatch criteria. RESULTS:Many different types of school furniture were presented at the schools. Also, a high level of mismatch was registered for seat height, desk height and seat-to-desk clearance. Finally, the analysis of all considered dimensions together showed that there was a high level of cumulative mismatch. CONCLUSIONS:It can be concluded that there were high levels of mismatch between the school furniture and student anthropometric characteristics and that this mismatch varied within the difference types of schools. This situation may have occurred because furniture acquisition was made without considering any ergonomic criteria.